MENJADI TERANG DI RUANG KELAS INTEGRASI TEOLOGI KRISTEN DALAM PRAKTIK KEGURUAN DAN PENDIDIKAN KRISTEN - Jhemi Erianto; Grace; Windra Wulan Sari; Ega Astri Minanga; Febrianti Sule (JIP: Jurnal Ilmu Pendidikan, 2026)
This article discusses the integration of Christian theology into Christian teaching and education practices using the concept of “being a light in the classroom” as a theological and pedagogical framework. Christian education is understood not only as a process of knowledge transfer, but as an effort to form a whole person encompassing intellectual, moral, spiritual, and social dimensions. This article aims to examine the theological basis of the concept of the light of the world, the role of Christian teachers as agents of transformation, the integration of Christian theological values ​​in learning strategies and methods, and the challenges and opportunities for Christian education in the context of contemporary education. This research uses a qualitative approach with a literature study method of relevant and credible Indonesian-language theology and Christian education literature. The analysis was conducted descriptively and interpretively to identify theological principles that can be applied in educational practice. The results of the study indicate that the theology of the light of the world provides a strong foundation for Christian education in delivering meaningful and transformative learning.